Phospholipase D signaling is essential for meiosis. - Rose, K (1995)
Phospholipid metabolism plays an important role in cellular regulation by generating second messengers for signal transduction. Many stimuli activate a phospholipase D, which catalyzes the hydrolysis of phosphatidylcholine, producing phosphatidic acid and choline. Here we report that the yeast SP014 gene, which is essential for meiosis [Honigberg, S. M., Conicella, C. & Esposito, R. E. (1992) Genetics 130, 703-716], encodes a phospholipase D. SP014 RNA and protein activity are induced during late meiotic prophase, and the enzyme has properties similar to mammalian phosphatidylinositol 4,5-bisphosphate-regulated phospholipase D. Characterization of an unusual allele of SP014 defines regions of the protein important for enzyme catalysis and regulation. These results implicate phospholipase D signaling in regulating cellular differentiation.